Actualization of Karang Taruna in Implementing Entrepreneurial Values ​​in Drajat Village, Kesambi District, Cirebon City (A Social Science and Entrepreneurship Journal, 2024)
This study aims to find out and describe the actualization of Karang Taruna in implementing entrepreneurial values, driving and inhibiting factors, and the strategy of Karang Taruna Pangeran Drajat in actualizing entrepreneurial values. This research is a qualitative research with the technique used is a snippet of purposive sampling. Data collection techniques with interviews, observations and document analysis. Data validity uses data/source triangulation techniques and triangulation methods. Data analysis uses an interactive analysis model. Based on the results of the study, it can be concluded that the actualization of Karang Taruna Pangeran Drajat in implementing entrepreneurial values is to be able to see opportunities, optimism, able to take risks, creative and innovative, commitment, and proactive, these values are applied to every entrepreneurial activity. Then the driving and inhibiting factors in actualizing entrepreneurial values include, driving factors: environmental conduciveness, skills and knowledge, motivation and commitment, inhibiting factors: capital problems, managerial problems, business location problems. Then the strategy of Karang Taruna in implementing entrepreneurial values includes: education and training, communication and practice, believing in ability.
Keywords: Actualization; Entrepreneurial Values; Karang Taruna